2014
DOI: 10.1111/joim.12288
|View full text |Cite
|
Sign up to set email alerts
|

Steroid plus antiviral treatment for Bell's palsy

Abstract: Abstract. Kang HM, Jung SY, Byun JY, Park MS, Yeo SG (Kyung Hee University, Seoul, Korea). Steroid plus antiviral treatment for Bell's palsy. J Intern Med 2015; 277: 532-539.Objectives. The effectiveness of antiviral agents for the treatment of Bell's palsy is uncertain. We evaluated whether a steroid with an antiviral agent (S + A group) provided better recovery outcomes than a steroid alone (S group) in patients with Bell's palsy.Subjects and design. A total of 1342 patients diagnosed with Bell's palsy who v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
0
15
0
5
Order By: Relevance
“…The literature so far has been presenting very contradictory results. [13][14][15][16] Ocular protection has to be emphasised to prevent lesions of the cornea and conjunctiva, which are very frequent in these cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature so far has been presenting very contradictory results. [13][14][15][16] Ocular protection has to be emphasised to prevent lesions of the cornea and conjunctiva, which are very frequent in these cases.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have sought to use antiviral agents, corticoids, rehabilitation and even surgical decompression of the nerve in search of some significant result. The literature so far has been presenting very contradictory results . Ocular protection has to be emphasised to prevent lesions of the cornea and conjunctiva, which are very frequent in these cases.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies and guidelines were recommended that combined treatment maybe a good choice. [26,27] Our study showed that the use of steroids plus antivirals and the use of steroids plus mecobalamin are 2 good choices.…”
Section: Discussionmentioning
confidence: 85%
“…Various types of therapeutic approaches are available, but the effectiveness of definitive treatments are unknown. 17 The traditional systemic corticosteroid therapy in acute peripheral Bell's palsy in patients with DM type 2 can cause hyperglycemia, and local therapy is required as an alternative treatment approach. 18,19 Palsy could be treated by corticosteroids up to the rate of 17% in a complete recovery by treatment difference.…”
Section: Discussionmentioning
confidence: 99%